Review of 2011 financial sector operational plan. (Water Briefs., 2017)
The cross cutting impact of finance on different sectors and economic activities amplifies opportunities for expanding financial inclusion and poverty reduction, which is why ADBs 2011 Financial Sector Operational Plan (FSOP) was designed to address challenges ahead. ADBs finance sector operations contributed 11% of total lending portfolio over 20112015, about 15% of that in 2015 alone. This review examines the implementation of the 2011 FSOP and looks at the critical role of the finance sector in development in Asia and the Pacific. While this publication affirms that the FSOP remains valid and relevant, it also makes recommendations up to 2020 and provides a platform to launch the FSOP beyond 2020 to ensure its relevance with ADBs Strategy 2030.